2013
DOI: 10.1590/s1415-47572013005000006
|View full text |Cite
|
Sign up to set email alerts
|

Protection against laryngeal and pharyngeal carcinoma: Heterozygous vs. homozygous deletions of GSTM1 and GSTT1

Abstract: Deletions in GSTM1 and GSTT1 genes are considered to be a risk factor for cancer development but the exact location of these deletions in the genome was unknown. Three main objectives of the current study were to: (a) identify the boundaries of these deletions in the human genome, (b) screen homozygous (−/−) and heterozygous (+/−) deleted, as well as homozygous present (+/+) individuals using PCR assays, (c) detect associations of pharyngeal (PC) and laryngeal cancer (LC) with the respective genotypes. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Meanwhile, individuals of Hispanic origin exhibit GSTT1 deletions at a rate of 10-12 percent (149)(150)(151)(152). In terms of ethnicity, Asians are more susceptible to HNC associated with GSTT1 null genotype, compared to their European and American counterparts (101). The present meta-analysis reported that GSTT1 polymorphism has an association with the risk of HNC in Asian and mixed ethnicities, not Caucasians.…”
Section: Discussionmentioning
confidence: 46%
“…Meanwhile, individuals of Hispanic origin exhibit GSTT1 deletions at a rate of 10-12 percent (149)(150)(151)(152). In terms of ethnicity, Asians are more susceptible to HNC associated with GSTT1 null genotype, compared to their European and American counterparts (101). The present meta-analysis reported that GSTT1 polymorphism has an association with the risk of HNC in Asian and mixed ethnicities, not Caucasians.…”
Section: Discussionmentioning
confidence: 46%